Pertanggungjawaban Pengobatan Tradisional Dinilai Dari Aspek Hukum Kesehatan - Abdurrahman; Bahtiar Husain; Budi Purnomo (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The development of traditional medicine service providers has experienced rapid growth over time. Increasing public demand has caused the traditional medicine industry to increase in 2020. To accommodate consumer protection and the provision of traditional medicine, the government has issued legislation regarding traditional health providers, especially Law no. 17 of 2023 (previous law Law No. 39 of 2009 concerning health) and other government regulations that support the health law. The existence of cases of traditional medical service providers endangering the lives of their patients means this research will examine the responsibilities of traditional health service providers in accordance with the Health Law. This research uses a qualitative descriptive method with a normative legal research model. This method was chosen because it can thoroughly describe the research topic. Data was obtained from statutory regulations, government regulations, ministerial regulations, and other documents related to the research topic. The research results show that the Health Law (new or old) has regulated criminal liability for providers of traditional healing services. However, the explanation portion is different because some regulations have been discussed in Government Regulations. On the other hand, to reduce potential losses, people need to choose trusted service providers and learn about consumer rights to traditional health service